Text learning model description using literature text - Syahrul R, Novelti, (Opción, 2019)
This study aimed at producing a description text learning model using literary text. The instruments used were interviews, observations, questionnaires, questionnaires, and tests. As a result, the quality of learning devices from three aspects, namely: validity, practicality, and effectiveness. The validity of the learning device is based on the results of the students' descriptive text exam. In conclusion, the teacher needs to design a learning model so that students follow learning without feeling forced and pleasant and learning tools consist of lesson plans, short story texts, and learning test results.